Saving and Empowering Young Lives in Europe (SEYLE): a randomized controlled trial - Wasserman, Danuta; Carli, Vladimir; Wasserman, Camilla; Apter, Alan; Balazs, Judit; Bobes, Julia; Bracale, Renata; Brunner, Romuald; Bursztein-Lipsicas, Cendrine; Corcoran, Paul; Cosman, Doina; Durkee, Tony; et al. (BMC public health, 2010)
There have been only a few reports illustrating the moderate effectiveness of suicide-preventive interventions in reducing suicidal behavior, and, in most of those studies, the target populations were primarily adults, whereas few focused on adolescents. Essentially, there have been no randomized controlled studies comparing the efficacy, cost-effectiveness and cultural adaptability of suicide-prevention strategies in schools. There is also a lack of information on whether suicide-preventive interventions can, in addition to preventing suicide, reduce risk behaviors and promote healthier ones as well as improve young people's mental health.
Gesehen am 11.10.2023